A randomized, controlled, pragmatic trial of an iPad-based, tailored messaging intervention to increase human papillomavirus vaccination among Latinos. Issue 7 (3rd August 2019) - Dempsey, Amanda F.; Maertens, Julie; Sevick, Carter; Jimenez-Zambrano, Andrea; Juarez-Colunga, Elizabeth
ABSTRACT: Human papillomavirus (HPV) causes a number of cancers that disproportionally affect Latinos yet there is a paucity of research on interventions to increase HPV vaccination among this population. We sought to evaluate the efficacy of a web-based, individually customizable intervention, called CHICOs (C ombatting H PV I nfection and C ancers, tailored intervention) for its impact on HPV vaccine utilization. We conducted a three-armed, randomized, controlled trial in the waiting rooms of five family medicine practices from June 2014-February 2016 where CHICOS was compared to an iPad-based version of the Vaccine Information Sheet from the Centers for Disease Control and Prevention (untailored intervention), and usual care. Pair-wise comparisons between study arms of 6 different measures of HPV vaccine uptake were assessed, with analyses stratified by adolescents versus young adults. Of the 1, 294 participants enrolled in the study, 1, 013 individuals could be assessed for vaccination. Across study arms, 265 adolescents, but only 18 young adults, received an HPV vaccine dose during the study period. In both intention-to-treat and per-protocol analyses there were essentially no differences between the CHICOS and untailored arms in any vaccination measure, or between the untailored or CHICOS arms and usual care. Our study suggests that a tailored educational intervention may not be effective for increasing HPV vaccine uptake among Latino adolescents or young adults. However, the higher than expected baseline levels of positive vaccination attitudes of study participants could have diminished the statistical power of the study. Trial Registration Number: ClinicalTrials.gov (NCT02145156).